Analisis Ilustrasi Dolanan pada Kemasan Tehbotol Sosro Tahun 2024 - Nurantika, Melda; Laksani, Hening (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
The ever-growing creativity of product packaging design has an important role in attracting consumers. Tehbotol Sosro is one of the brand that promotes Indonesian culture through an annual packaging design competition, especially in 2024 with one of the winners being Dolanan illustration. The research aims to analyze the 2024 packaging illustration using Robin Landa's design principles. The descriptive qualitative research method with interactive models in data analysis consists of 4 stages, namely data collection, data reduction, data presentation, and conclusion. The results of the analysis were found to be asymmetrical, there was no visual hierarchy and emphasis, a repetitive rhythm of shapes, lines, and colors gave a monotonous impression, a consistent unity of visual style, and fulfilled the 5 laws of perception organization. The result is an illustration that fulfills almost all design principles. The existence of illustrations of traditional games is not only for aesthetics, but also a part of cultural revitalization by reviving and introducing traditional games with meaningful visuals.